55 years German society of anaesthesiology and intensive care medicine : Tradition and innovation - Schuttler, J. (Springer Berlin Heidelberg, 2012)
This book presents to all those who are interested in the history of Anaesthesiology historical details and information on the development of anaesthesiology in Germany and the remarkable growth of our Society. At the founding session of the German Society of Anaesthesia in Munich on 10 April 1953 42 persons had signed the founding documents. Today about 12,000 anaesthetists are members of the German Society of Anaesthesiology and Intensive Care Medicine, making the DGAI the biggest national society within ESA.   Well known are the pioneering contributions of German scientists and surgeons to the development of general, regional and local anaesthesia during the 19th and the beginning of the 20th centuries. But less known outside Germany are the reasons for the delayed evolution of anaesthesiology as a specialty of  its own in German medicine, far later than in the UK, Scandinavia or the USA. In this book you will find answers to this question and detailed information on the successful evolution of anaesthesiology especially at the Faculties of Medicine at German universities.